THE DISCUSSION ABOUT INFLUENCE OF OTHERS TOWARS CAR PURCHASE INTENTION - Tanzil, Devina; Belgiawan, Prawira Fajarindra (Journal of Business and Management, 2018)
Abstract. The increase of number of car ownership contributes to the increase of traffic congestion. Many studies on car ownership intention in Indonesia particularly on the effects of attitudes and norms. Previous research found that subjective norms and attitudes significantly influence someone’s intention to purchase a car. To be specific, reference group such as parents and friends of the respondent significantly influence car purchase intention. However, the previous research did not directly survey them, but only got the result from child perception of their parents. Therefore, to confirm whether parents and friends significantly influence purchase intention, they are also being surveyed. The objective is to diagnose that Parents’ and friends’ attitude is significantly influence respondents’ attitude towards their decision on car purchase intention. Data collected using a quantitative method with convenient sampling technique. The questionnaire was spread online to 200 respondents includes father, mother, and friend. The researcher only asked the respondents about their attitudes towards car, socio-demographic, and the intention to own a car for the future. Then, the data is analyzed using principal component analysis, linear regression, and ordinal regression. The result shows that several factor of parents’ and friends’ attitude significantly influence respondent attitude towards car purchase intention. Background: Belgiawan et al. (2017) found that attitudes significantly influence someone’s intention, they also found similarly that the parents of their respondent significantly influence car purchase intention. However, their research and mostly other research inline (Casaló and Escario 2016; Flay et al., 1994) did not ask directly to the significant others, they only got the result from child perception of their significant others. These might indicate a bias since the information of influence is only a proxy for what might be the actual influence. Therefore, it is also important to understand influence from the perspective of the influencers themselves. Methods: The data for this research was collected using Quantitative Method approach through online questionnaire to 200 respondents includes mother, father, and friend which means there are 50 sets of family. This study, adopt the Principal Component Analysis, Linear Regression, and Ordinal Regreesion to see the relationship between significant others to ones’ attitudes and one’s decision to purchase a car. Results: From the calculation using SPSS, researcher got five factors of child attitude towards car but only several factor of significant others’ attitude result are significant influence child’s attitude. Beside, from six varibles there are four variable that have a significant relationship between significant others advice and hope on one’s decision to purchase a car. Conclusion: The purpose of this paper is to analyze the significant others (father, mother, and friend) are influence one decision or not and to diagnosing the significants’ other attitude is significantly influence one’s attitude or not. But this paper is focusing on car purchase intention. This research found that parents’ attitude towards car is significantly influence childs’ attitude and this result can be used to strengthen the previous research result who said that parents attitude is significantly influence one’s attitude by asking the parents’ and friend directly, since the previous research only rely on childs’ perception towards their parents attitude. Because of the purpose of this paper is analyzing one’s attitude towards car, so the result can be used by car company to increase or improve the purchase intention and can create a good marketing communication.Keywords: Attitudes, Cars Company, Significant Others, Perception, Purchase Intention.